Perubahan Sifat Kimia Tanah Ultisol Setelah PanenPadiGogo (Oryza Sativa L.) Yang Diaplikasi Biochar - Faisal, RE; Nelvia, Nelvia; Nurbaiti, Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
The research aim to study the change of ultisol soil chemical properties after crop upland rice (Oryza sativa L.) that applied biochars from agricultural waste as rice husk and shell of coconut. The research was conducted at Agricultural Faculty Experimental Unit and soil laboratory, university of riau, pekanbaru city. The research was conducted experimentally with a completely randomized design by one factor. The factor is dose of biochar that consists of 4 levels (without biochar, 25 g/polybag rice husk biochar, 25 g/polybag coconut shell biochar, 25 g/polybag biochar mixture both) each was repeated 3 times so that there were 12 units of experimental sample. The parameter observed of ultisol soil chemical were number of soil pH (pH meter), number of C-organic (Walkley and Black), number of N total (Kjeldahl), number of P total (HCl 25%), number of K total (HCl 25%), number of KTK (Leaching), number of bases can be exchanged (Atomic AdsorbenSpectrotometer/AAS), number of Al dd dan number H dd (KCl 1N). the result showed that aplicationbiochars with dose 25 grams/polybag can not significant at all number of parameters but only 2 parameters are significant like number of N total (Kjeldahl), and number of P total (HCl 25%). the result parameters that significant is still low so it must do processing to be able for sustainable agriculture.Keywords :Ultisol soil chemical, biochar, upland rice